Validation of reference materials for uranium radiochronometry in the frame of nuclear forensic investigations. (August 2015) - Varga, Z.; Mayer, K.; Bonamici, C.E.; Hubert, A.; Hutcheon, I.; Kinman, W.; Kristo, M.; Pointurier, F.; Spencer, K.; Stanley, F.; Steiner, R.; Tandon, L.; et al.
Abstract: The results of a joint effort by expert nuclear forensic laboratories in the area of age dating of uranium, i.e. the elapsed time since the last chemical purification of the material are presented and discussed. Completely separated uranium materials of known production date were distributed among the laboratories, and the samples were dated according to routine laboratory procedures by the measurement of the 230 Th/ 234 U ratio. The measurement results were in good agreement with the known production date showing that the concept for preparing uranium age dating reference material based on complete separation is valid. Detailed knowledge of the laboratory procedures used for uranium age dating allows the identification of possible improvements in the current protocols and the development of improved practice in the future. The availability of age dating reference materials as well as the evolvement of the age dating best-practice protocol will increase the relevance and applicability of age dating as part of the tool-kit available for nuclear forensic investigations. Highlights: A methodology for preparing uranium age dating reference material was validated. Detailed laboratory procedures for uranium age dating are summarized. The difficulties and further developments of uranium age dating are demonstrated.